Rising Burden of Obesity in Asia - Ambady Ramachandran; Chamukuttan Snehalatha (Hindawi Limited, 2010)
Overweight and obesity have reached epidemic proportions in many Asian countries. These countries also face a grave burden of obesity-related disorders such as diabetes, hypertension, and cardiovascular diseases, which develop at a younger age than in Western populations. These disorders are also manifested in childhood. The major causative factors are related to the lifestyle changes occurring due to rapid socioeconomic transition. Asian populations show several differences in genetic factors when compared with the white population, and they also have lower cut points for environmental risk factors. National programmes targeting public awareness, education and improved structural facilities to facilitate healthy lifestyle are the keys to alleviate the economic and health care burden of the obesity-related disorders.